(untitled) (Environmental Science Journal (esjo) : Jurnal Ilmu Lingkungan, 2025)
The Pinus Ciherang area, located in Sukamukti Village, Cisayong District, Tasikmalaya Regency, at the foot of Mount Galunggung, holds great tourism potential, particularly with the presence of beautiful pine forests and the waterfalls Curug Badak and Curug Ciherang. However, this exceptional potential has not been well managed, mainly due to the local community’s lack of awareness about the valuable assets in their surroundings. As a result, the area has not developed optimally. To realize this potential and address the issue of unorganized management, a holistic development strategy needs to be implemented. The objective of this study is to formulate a sustainable development strategy for the Pinus Ciherang nature tourism area through the identification of local potentials, community empowerment based on Community Based Tourism (CBT), and the application of the 4A concept (Attraction, Accessibility, Amenity, and Ancillary) along with digital innovation to enhance the local economy. This study uses a literature review method. The approach involves applying the 4A strategy and the principles of Community Based Tourism (CBT). Through the 4A strategy, natural attractions such as pine forests and waterfalls can be optimized, accessibility to the location improved, supporting facilities for tourists provided, and appropriate service institutions established.